Removal of Metaphyseal Screw Only After Hemiepiphysiodesis Correction of Coronal Plane Deformities Around the Knee Joint: Is This a Safe and Advisable Strategy?. Issue 3 (March 2019) - Keshet, Doron; Katzman, Alexander; Zaidman, Michael; Eidelman, Mark
Abstract : Purpose: Correcting lower limb angular deformities in the skeletally immature patient with guided growth is a very common procedure. Using an 8-plate construct to produce reversible hemiepiphysiodesis allows correction of the mechanical axis of the limb. It has become routine strategy to remove only the metaphyseal screw from the 8-plate construct after desired correction is achieved, in order to ease its reinsertion in case of deformity recurrence. In this study, we evaluated the efficacy and safety of this technique. Methods: We reviewed the results of 80 patients (133 limbs) who were treated by guided growth using 8-plate hemiephisiodesis around the knee. After achievement of the correction goal, both screws and plate were removed in 78 limbs while only the metaphyseal screw was removed in 55 limbs. Results: The mean age of patient was 8.9 years at the time of surgery. Within the group whose metaphyseal screw was removed, 12 limbs showed radiographic signs of deformity recurrence and underwent reinsertion of the metaphyseal screw. In 9 of the cases of metaphyseal screw reinsertion, the plate or its location had to be changed (mean follow-up after screw removal was 14 mo). There were 2 cases where leaving the plate with an epiphyseal screw caused a radiographic bone bar and undesired clinical growth arrest. Conclusions: On the basis of our experience, leaving the 8-plate construct with an epiphyseal screw in place exposes the patient to risks of bony bar, growth arrest, and an additional surgery for hardware removal. The majority of 8-plate constructs are not suitable for reinsertion of the metaphyseal screw.